Analisis Kelayakan Bisnis Usaha Teh Papua (Vernonia amygdalina) - Handjojo, Eko Suwito; Syarief, Rizal; Sugiyono, - (Institut Pertanian Bogor, 2017)
Various kinds of tea can be used as food and anti-diabetic medicine. One of plants that can be used as medicinal subtancesis Teh Papua (Vernonia amygdalina). Teh Papua, as become one of the local wisdom in Papua, has been used for generations to medicate malaria epidemic and blood sugar disease. Hence, good bussiness planning review will be needed to develop this potential plant. The purpose of this study is to analyze the feasibility of small Teh Papua industry. Descriptive research method was used in this research. Data are collected by observation, survey, and depth-interview with the bussiness actor. Aspects observed in this studyare aspects of market, marketing, technical and technological, organiza-tional and also management. Measurement of financial aspectfeasibility in this study is using Net Present Value (NPV), Internal Rate of Return (IRR), Net Benefit-Cost Ratio (Net B/C ), and Payback Period (PP). The result shows commercial financial analysis of Teh Papua indicates a positive NPV value of Rp. 316 068 835, IRR value of 45.17%, net value B/C of 2.48 and Payback Period of 17% and 27% depreciation.